The Role and Function of the Administrative Court in Resolving Disputes Over Permits for Places of Worship - Saragih, Yessi Nadia Giatma; Erliyana, Anna (UNIVERSITAS PAKUAN, 2019)
In addition to serving as the legality of spatial utilization and urban control, the Building Permit for Places of Worship (IMB Rumah Ibadah) also functions as an assurance of religious harmony as stated in Article 2 and Article 3 of the Joint Regulations of the Minister of Religious Affairs and the Minister of Home Affairs of the Republic of Indonesia Number 8 of 2006/Number 9 of 2006 on Guidelines for the Implementation of the Duties of Regional Head/Vice Regional Head in Maintaining Religious Harmony, Empowering the People's Forum for Religious Harmony, and Establishing Houses of Worship. Ideally, the establishment of a house of worship that complies with applicable procedures and rules can help avoid conflicts among religious adherents. In reality, there are issues during the establishment of churches that have led to lawsuits in the Administrative Court, such as the rejection of the building permit (IMB) for the Catholic Church of St. Stanislaus Kostka Kranggan and the suspension of the building permit for GKI BaPos Taman Yasmin. The purpose of this article is to examine the function and role of the Administrative Court in resolving disputes related to church permits. The research method used in this study is juridical normative, and the article is analyzed descriptively based on secondary data, namely literature review. The results of this study indicate that the Administrative Court has carried out its function and role in resolving disputes over church permits. However, some decisions cannot be properly executed.